C3a and Its Receptor C3aR Are Detectable in Normal Human Epidermal Keratinocytes and Are Differentially Regulated via TLR3 and LL37 - Susanne Mommert; Lisa Doenni; Phillip Szudybill; Christoph Zoeller; Frerk Hinnerk Beyer; Thomas Werfel (Journal of Innate Immunity, 2021)
To study the molecular interplay between TLRs and complement representing ancient danger-sensing mechanisms, we examined the regulation of the C3a/anaphylatoxin C3a receptor (C3aR) axis in normal human epidermal keratinocytes (NHEKs) by treatment with different TLR ligands. Protein staining followed by flow cytometry revealed highly constitutive intracellular expression levels of the C3aR in NHEKs. Stimulation with Poly I:C up-regulated C3aR mRNA and intra- and extracellular expression in NHEKs which showed functional relevance by up-regulating CXCL10 and down-regulating C3 expression in response to C3a. mRNA and protein levels of C3 and protease cathepsin L (CTSL) that can cleave C3 were up-regulated by the TLR3 ligand Poly I:C. Enhanced intracellular expression levels of the biologically active C3 fragment (C3a), in response to TLR3 stimulation were also detectable in NHEKs. Cathelicidin antimicrobial peptide LL-37 potentiated Poly I:C-induced C3aR, C3, and CTSL up-regulation. In conclusion, we point to a role of TLR3 to promote up-regulation of C3aR, C3, and CTSL expression levels and generation of C3a. Our data provide evidence that local generation and activation of complement components as described for T cells or myeloid cells represent a scenario which may take place in a similar way in NHEKs.